Understanding and assessing dental anxiety and fear in Malaysia / Rashidah Esa - Rashidah, Esa (2021)
Dental anxiety refers to a vague, unpleasant feeling that something undesirable awaits whereas dental fear is a normal response to a threat or danger. Anticipation of a dental visit can induce dental anxiety whereas the most fear-provoking situations were the sight of injection needles and the drilling procedures. Nevertheless, the terms are often used interchangeably. Dental anxiety and fear (DAF) are perpetual problems worldwide and their assessment is important to assist dentists in the management of highly anxious patients. In Malaysia, more studies are needed to add to the growing body of DAF research. The aim of this thesis was to explore different aspects of DAF and their associated factors among adolescents, ante natal mothers, preschool children and their mothers. A series of study was conducted to achieve the aim. In the ante natal study, 407 mothers from Negeri Sembilan participated. The adolescent study comprised of 503, 16- year-old schoolchildren from Penang. In both these studies, the questionnaire consisted of participantsï¿½ demographic profile and the Kleinknechtï¿½s DFS. Two separate studies were conducted to assess the psychometric properties (validity and reliability) of the Malay-Early Childhood Oral Health Impact Scale (Malay-ECOHIS) and the Malay Modified Child Dental Anxiety Scale (Malay-MCDASf).In the mother-child dyad study, 842 complete data were obtained from 24 kindergartens in two districts in Selangor. Mothers answered the questionnaire on socio-economic status, the Malay-Modified Dental Anxiety Scale (Malay-MDAS), and the Malay-ECOHIS to assess maternal perception of impact on childï¿½s oral health-related quality of life (COHRQoL). Child's dental anxiety was assessed using the Malay-MCDASf. The clinical examination consisted of the DMFT/dmft as the outcome measure of dental caries disease and treatment experience. iv The overall prevalence of dental fear among ante natal mothers was 94.1%. However, 67.6% had low fear, whilst 26.5% were moderately fearful. Among 16-year-old adolescents, 46.7% were moderately fearful and the mean DFS score was 40.8. None of the ante natal mothers and adolescents reported high fear. The prevalence of high dental anxiety in the sample of mother-child dyads were 8.7% and 53.9% respectively. Significant relationship between dental anxiety and dental decay experience in adolescents, antenatal mothers and mother-child dyads were established. Dentally anxious participants had more dental decay and higher overall DMFT/dmft. Adolescents from rural areas reported having significantly higher fear. Maternal dental anxiety and child dental caries showed significant impact on COHRQoL, child impacts section (CIS) and family impacts sections (FIS). Demographic factors such as education, income, urban/rural location, and public/private kindergarten acted as moderators that modify the strengths of the maternal dental anxiety-COHRQoL relationship. However, child dental anxiety does not have any significant direct impact on COHRQoL, CIS, FIS, or child dental caries. In summary, DAF is quite common among all the studied populations. The prevalence of child dental anxiety was high. Treating DAF at an early age can produce positive outcomes and improve the quality of life. There is a need to establish the norms cut-off points for the different DAF indices. Future research requires development of more complex models to further understand the dynamics of DAF and their associated factors. Keywords: dental anxiety, dental fear, dental caries, psychometric, quality of life